Geriatric Depression Scale (GDS-15 and GDS-5): A study of the internal consistency and factor structure - Gómez Angulo, Carine B.; Corporación Universitaria Iberoamericana (Pontificia Universidad Javeriana, 2010)
Background: The Geriatric Depression Scale (GDS), 5- and 15-item version, are useful for identify depressive symptoms among elder people. However, psychometric properties of a version of five items has not explored among Colombian elders. Objective: To study the internal consistency, factor structure and construct reliability of the GDS-15 and GDS-5. Method: A total of 105 Colombian people over 65 year-old participated. Internal consistency, construct reliability and exploratory factor analysis were computed. Results: The GDS-15 showed internal consistency of 0.78, construct reliability of 0.87 and two-dimensional structure. The GDS-5 exhibited internal consistency of 0.73, construct reliability of 0.83 and one-dimensional structure. Conclusions: The GDS-5 shows better psychometric properties than the GDS-15. It is needed to design a new and more reliability scale